An assessment of food overlap between gibbons and hornbills - Chuti on Kanwatanakid-Savini (2018)
Hornbills and gibbons are considered to be potential competitors for food. They show considerable overlap in their frugivorous diet, foraging site (outer part of tree crowns), and reproductive period. However, the extent and nature of such overlaps have never been measured. Here we characterize the dietary overlap of the Great Hornbill, Wreathed Hornbill, Oriental Pied Hornbill, White-throated Brown Hornbill and White-handed Gibbon based on a long-term data on their feeding ecology at Khao Yai National Park, Thailand. Results from a Correspondence Analysis showed a slight overlap between the diets of the hornbills and gibbon, which may be attributed primarily on the dietary consumptions of Ficus spp. and, to a lesser extent, Polyalthia viridis. Due to the large crown size of Ficus and the overall low nutritional quality of its fruits, we hypothesized that a dietary overlap between the hornbills and gibbon for Ficus is energetically inconsequential for either groups. In contrast, P. viridis has comparatively small crowns, is present in the site in low densities, and produces fruits high in protein. Therefore, the overlap in diet between hornbills and gibbon for P. viridis may create the basis for competition, which in any event will be limited to pseudo-interference. © National University of Singapore.